2018
DOI: 10.15171/ijhpm.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Doctors in Rural Bangladesh: A Policy Analysis

Abstract: Background: Retaining doctors in rural areas is a challenge in Bangladesh. In this study, we analyzed three rural retention policies: career development programs, compulsory services, and schools outside major cities – in terms of context, contents, actors, and processes. Methods: Series of group discussions between policy-makers and researchers prompted the selection of policy areas, which were analyzed using the policy triangle framework. We conducted document and literature reviews (1971-2013), key informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…A policy analysis on the human resources for health in Bangladesh also revealed that the DGHS is principally managed by the clinicians at the expense of public health experts. At the MoHFW level, the top health-bureaucrats are mostly drawn from other ministries, often unrelated to the health sector 26 . Another theme that emerged as the determinant of health system trust was leadership, both in the health system and the political sphere.…”
Section: Discussionmentioning
confidence: 99%
“…A policy analysis on the human resources for health in Bangladesh also revealed that the DGHS is principally managed by the clinicians at the expense of public health experts. At the MoHFW level, the top health-bureaucrats are mostly drawn from other ministries, often unrelated to the health sector 26 . Another theme that emerged as the determinant of health system trust was leadership, both in the health system and the political sphere.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these barriers that healthcare providers face, rural patients en-Open Journal of Obstetrics and Gynecology counter significant barriers in accessing those providers. While nearly 70% of the population in Bangladesh lives in rural areas, less than 20% of healthcare workers provide medical care in these areas [20]. This leaves patients turning to untrained providers and a substantial burden being placed on providers practicing in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…1 This research not only helps understand the healthcare personnel challenges in Ireland but also provides an alternative viewpoint through which to understand how the prevailing global healthcare worker crisis is unfolding, and implications that this has for healthcare worker motivation and retention in healthcare human resources systems in developed, mostly the Organisation for Economic Co-operation and Development (OECD), and developing countries, mainly in sub-Saharan Africa and South East Asia. [2][3][4][5][6] This article is also an important addition to the discussion about healthcare worker migration and what the failure to retain medical graduates in some first-world countries such as Ireland may mean in the endeavour to uphold principles set by the World Health Organization (WHO) Global Code on International Recruitment of Health Personnel. 7,8 Further, and most importantly, this article contributes to the understanding of what the challenge of healthcare graduates' migration may mean to the formulation, implementation and evaluation of retention strategies towards the realisation of HRH policy outcomes outlined by the 2018 Astana Declaration, and the HRH Global Strategy (Workforce 2030).…”
mentioning
confidence: 99%
“…Rather globalisation, less favourable working conditions in the least developed parts of the world, health worker shortages in the face of increased demand for healthcare specialists mainly as a result of more favourable socio-demographic outcomes amongst the population in the more developed parts of the world and the portable nature of medical qualifications makes the migration of early-career medical doctors inevitable. [1][2][3][4][5] My point in this is that healthcare personnel shortages and the failure to retain young medical doctors in any one country in the developed world is one driver of doctor migration from the already fragile healthcare worker systems in the third world. This pattern of health personnel migration has a less favourable effect on the global health personnel strengthening agenda, and indeed the pursuit of universal health coverage at a world level.…”
mentioning
confidence: 99%
See 1 more Smart Citation